Persepsi Guru Terhadap Implementasi Kurikulum 2013 Pada Mata Pelajaran Seni Budaya dan Prakarya (SBdP) di SDN 13 Biru Kecamatan Tanete Riattang Kabupaten Bone - Awaluddin Muin; Sitti Jauhar; Wahni Wahni (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
This research is a descriptive qualitative research that aims to describe the teacher's perception of the implementation of the 2013 curriculum in arts and crafts subjects at SDN 13 Biru, Tanete Riattang District, Bone Regency. The subjects of this study were all 6 class teachers. The data collection instrument used an interview guide. Data analysis techniques in research are 1) Data collection, 2) Data reduction, 3) Data presentation and 4) Conclusion drawing. The results of the research obtained are that the preparation for SBdP learning at SDN 13 Biru is planned through teacher working group activities. SBdP learning is carried out in accordance with the plans that have been made using learning methods, strategies and media. The SBdP learning assessment is carried out for both the process and the results by involving cognitive, affective and psychomotor aspects. So it can be concluded that the teacher's perception in implementing the 2013 curriculum on SBdP subjects at SDN 13 Biru, Tanete Riattang District, Bone Regency is good because teachers have an understanding in planning, implementing and assessing learning.